PEMANFAATAN YOGURTSALESPRO SEBAGAI UPAYA PENINGKATAN TATA KELOLA PENJULAAN UMKM BARK FRUITY - Retno Damayanti; Usman Nurhasan; Anugrah Nur Rahmanto (P3M Politeknik Negeri Malang, 2025)
In the digital era, the transformation of information systems has become a crucial element in enhancing the competitiveness of micro, small, and medium enterprises (MSMEs). This community service initiative focuses on the digitalization of sales operations at Yogurt Bark Fruity, a student-run culinary business offering healthy yogurt-based products. Previously, sales activities were conducted manually via WhatsApp and Instagram, which posed risks of recording errors and limited market reach. The proposed solution involves the development and implementation of the yogurtSalesPro application, based on the PPEPP method. This system is designed to integrate the management of transactions, inventory, customer data, and sales reporting. Evaluation using the System Usability Scale (SUS) resulted in a score of 71.5, indicating a good level of usability. Additionally, assessment through the Technology Acceptance Model (TAM) revealed high scores across all indicators, with Perceived Usefulness and Perceived Ease of Use each achieving 100% positive responses. The application’s effectiveness is reflected in improved recording efficiency, a reduction in transaction errors from 15% to 2%, and an increase in both daily transactions and new customers. Beyond operational efficiency, the application also supports digital literacy and student entrepreneurship. Thus, yogurtSalesPro proves to be an effective solution in fostering innovation and sustainability for technology-based MSMEs.